2018
DOI: 10.1007/s11222-018-9818-2
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of variance parameters in non-standard generalised linear mixed models: application to penalised smoothing

Abstract: We present a novel method for the estimation of variance parameters in generalised linear mixed models. The method has its roots in Harville (1977)'s work, but it is able to deal with models that have a precision matrix for the random-effect vector that is linear in the inverse of the variance parameters (i.e., the precision parameters). We call the method SOP (Separation of Overlapping Precision matrices). SOP is based on applying the method of successive approximations to easy-to-compute estimate updates of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The model performance criteria reported in Table 1 show good model performance in terms of prediction accuracy in all scenarios. All criteria showed that slightly worse predictions where obtained in scenario 2, this is mainly due to the fact that, for consistency, we have used the same size of B-spline basis for all scenarios (those used in the data analysis), but in the case of rapidly changing spatial patters (as is the case in scenario 2), a larger basis would be necessary to correctly capture the spatial effect, or adaptive P-splines [ 43 ] could be used; however, this approach is beyond of the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The model performance criteria reported in Table 1 show good model performance in terms of prediction accuracy in all scenarios. All criteria showed that slightly worse predictions where obtained in scenario 2, this is mainly due to the fact that, for consistency, we have used the same size of B-spline basis for all scenarios (those used in the data analysis), but in the case of rapidly changing spatial patters (as is the case in scenario 2), a larger basis would be necessary to correctly capture the spatial effect, or adaptive P-splines [ 43 ] could be used; however, this approach is beyond of the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…( 5), might make estimation with the above-mentioned software computationally expensive. Thus, we have implemented in the R language 45 our own code (provided along with the paper), which resorts to the recently proposed SOP (Separation of Overlapping Penalties) method 46 . Empirical best linear unbiased estimates (BLUE) and predictors (BLUP) are obtained by the solution of Henderson's mixed model equations 47 , and variance components by means of restricted maximum likelihood (REML) 48 .…”
Section: Methodsmentioning
confidence: 99%
“…An extension of GAMLSS was used to model the positions that are not random, and the sample collection is carried out based on the shape and scale parameter allowing specific selection of parametrical distributions to the response variables (Wojtyś, Marra & Radice, 2018). In generalized linear mixed models, the parameters of variance were calculated, and the models were designed that had a precision matrix for the random influence vector following a constant of the variance factors (Rodríguez-Álvarez et al, 2019). TASSEL framework implemented various GWAS models such as Generalized Linear Models (GLM) and Mixed Linear Model (MLM) using a software GUI or through command-line.…”
Section: Non-linear Additive Modelsmentioning
confidence: 99%